Pengaruh Kepemimpinan Transfomasional, Work Life Balance dan Beban Kerja Terhadap Komitmen Organisasi - Thahir Maulana Abdillah; Aris Wahyu Kuncoro (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Organizational commitment is an important concept in human resource management. Organizations that want to achieve success need to understand the factors that influence organizational commitment and implement strategies to increase the organizational commitment of their employees. so that it can provide great benefits for the performance and success of the organization as a whole. The type of research used is quantitative research, with primary data collection methods using questionnaires taken from 51 respondents who are employees of PT. Luttan Indonesia Store. The data collection technique for this research uses multiple linear regression with the help of SPSS V.27 software. Based on the research results, it is known that (1) Transformational Leadership has a significant effect on Organizational Commitment, (2) Work Life Balance has no significant effect on Organizational Commitment, (3) Workload has a significant effect on Organizational Commitment. The contribution of this research pays attention to Transformational Leadership, Work Life Balance, Workload and Organizational Commitment